Resolusi Konflik Pembangunan New Yogyakarta International Airport di Temon Kulon Progo - Catur Wulandari; Krisnaldo Triguswinri (Jurnal Sosial Soedirman, 2018)
Conflict of the New Yogyakarta International Airport (NYIA) construction that appeared in KulonProgo Regency started in 2011 soon after the Indonesian government that represented by BUMN and Indian investor, GVK Power & Infrastructure, started the work. The problem was that the airport construction was done on a dense population villages and productive land field in Temon sub district of KulonProgo Regency. To build the NYIA, the construction was estimated would need 637 hectare of dense population land. Those included 6 villages that would be flattened. The long period of conflict was the effect of misunderstanding and unsmooth negotiation between the subject and the object of construction which were the government and the affected villagers. This conflict was getting worse as there were two sides among the villagers, pro and contra. These emerged vertical and horizontal conflict. Vertical conflict appeared between the villagers and the government. The contra side villagers assume that the government dispossesses their land field and their living space(socially and economically) for the NYIA. While the government argued that the establishment of NYIA was a national program that had been stated in RPJMN and would be implicated to the increasing quality of the surrounding community.